Genotyping and molecular detection of multidrug-resistant Mycobacterium tuberculosis among tuberculosis lymphadenitis cases in Addis Ababa, Ethiopia. (January 2018) - Zewdie, O.; Mihret, A.; Abebe, T.; Kebede, A.; Desta, K.; Worku, A.; Ameni, G.
Abstract: Multidrug-resistant tuberculosis (MDR-TB) has emerged as a major public health problem. Drug-resistance surveillance data show that 3.9% of new and 21% of previously treated TB cases were estimated to have had rifampicin/ multidrug-resistant tuberculosis (MDR/RR-TB) in 2015. This implies that the MDR-TB is increasing alarmingly. Hence, a better understanding of drug resistance mechanisms and genotypes associated with multidrug resistance in M. tuberculosis is crucial for improving diagnostic and therapeutic methods to treat individuals with MDR-TB. The aim of this study was to analyze molecular drug resistance mutations of MDR-TB isolates from the cases of TB-lymphadenitis in relation to its genetic lineages. A cross-sectional study was conducted on culture positive cases from July to October, 2014 in Addis Ababa, Ethiopia. Sixty isolates were included to analyze drug resistance mutated gene responsible for MDR-TB in relation to its molecular genotyping. Mycobacterial culture, GenoTypeMTBDR plus and Spoligotyping were used to undertake the study. Of 60 TBLN isolates, 8.3% were identified MDR-TB cases and one isolate was isoniazid mono-resistant. Eleven isolates in T3-ETH genetic sub lineage were sensitive to both RMP and INH, while only 2 isolates were MDR-TB. Most of the RMP- resistant isolates showed mutation in codon S531L and all isolates mutated in the katG gene conferring INH resistant strains had mutations in codon of S315T1. Screening for the rpoB and katG gene mutation of tuberculosis lymphadenitis is useful in Ethiopia for an early detection and treatment of MDR-TB. Besides, there is a drug resistance variation among different lineages of Tuberculosis lymphadenitis which has important consequences for the development of efficient control strategies.